2013
DOI: 10.1002/ajh.23523
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the TYMP gene is associated with the outcome of HLA‐identical sibling allogeneic stem cell transplantation

Abstract: Thymidine phosphorylase (TYMP), an enzyme involved in nucleotide synthesis, has been implicated in critical biological processes such as DNA replication, protection against mutations, and tissue repair. In this work, we retrospectively evaluated the influence of a polymorphism in the TYMP gene (rs112723255; G/A) upon the outcome of 448 patients subjected to allogeneic stem cell transplantation (allo‐SCT) from an human leukocyte antigen (HLA)‐identical sibling donor. The TYMP genotype of patients correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Targeting TYMP may be considered a potential immunotherapy for cancer. Guillem and colleagues recently provided the first epidemiological evidence of the TYMP gene SNP (rs112723255) effectively acting as a minor histocompatibility antigen [114]. This finding is in agreement with a previous study and suggests that TYMP is a potential target for cancer immunotherapy [115].…”
Section: The Role Of Tymp In the Development Of Chronic Diseasessupporting
confidence: 85%
“…Targeting TYMP may be considered a potential immunotherapy for cancer. Guillem and colleagues recently provided the first epidemiological evidence of the TYMP gene SNP (rs112723255) effectively acting as a minor histocompatibility antigen [114]. This finding is in agreement with a previous study and suggests that TYMP is a potential target for cancer immunotherapy [115].…”
Section: The Role Of Tymp In the Development Of Chronic Diseasessupporting
confidence: 85%
“…In patients with KIRC, a decreased expression of HADH was also related to immune infiltration and poor prognosis ( 58 ). TYMP, also known as a platelet-derived endothelial cell growth factor, catalyzes the reversible phosphorolysis of thymidine ( 59 ). TYMP was shown to be upregulated in multiple solid tumors, where it is implicated in cell proliferation and angiogenesis ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that the expression of TYMP was notably related to the expression of several immunocyte markers and might be involved in regulating the immune response. Many studies have indicated that TYMP was a potential target for cancer immunotherapy ( 59 , 61 ). Our study suggested that the prognostic value of these three LRGs in KIRC and the mechanism of the three genes in KIRC need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thymidine phosphorylase (TYMP), a platelet-derived endothelial cell growth factor, is overexpressed in tumor cells and surrounding extra matrix cells. It catalyzes the reversible phosphorolysis of thymidine [64] and is upregulated in multiple solid tumors [65]. This protein was associated with the expression of a number of immunocyte markers and may have a function in controlling the immunological response, indicating its potential relevance as an immunotherapy target [64,66].…”
Section: Metabolic Pathway Understandingmentioning
confidence: 99%